THE ANALYSIS OF FACTORS INFLUENCE THE PROFESSIONAL COMPETENCE OF ACCOUNTING TEACHER AT THE VACATIONAL SCHOOL IN LANGKAT REGENCY WITH MOTIVATION AS A MODERATING VARIABLE - Santi, Try (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze some factors which influenced professional competence of Accounting teachers at the SMK (Vocational Schools) in Langkat Regency with motivation as moderating variable. The research used causal associative method. The population was 45 SMK Accounting teachers in Langkat Regency as the respondents, and all of them were used as the samples (total sampling). Primary data were gathered by distributing questionnaire to the respondents and analyzed by using multiple regression analysis and residual test. The result of the research showed that educational background, training  and development, academic supervision, compensation, and the use of information technology and communication simultaneously had positive and significant influence on professional competence of SMK Accounting teachers in Langkat Regency. Partially, educational background, training, and development had positive and significant influence on professional competence of SMK Accounting teachers in Langkat Regency, while academic supervision, compensation, and the use of information technology and communication did not have any significant influence on SMK Accounting teachers in Langkat Regency. Motivation was not able to moderate the correlation of educational background, training and development, academic supervision, compensation, and the use of information technology and communication with professional competence of SMK Accounting teachers in Langkat Regency